Association between body mass index at diagnosis and outcomes in Chinese children with newly diagnosed acute lymphoblastic leukemia. (27th September 2022) - Hu, Wenting; Cheung, Yin Ting; Tang, Yanjing; Hong, Li; Zhu, Yuan; Chen, Jing; Wang, Zhuo; Zhou, Min; Gao, Yijin; Chen, Jing; Li, Benshang; Xue, Huiliang; et al.
Abstract: Purpose: Studies of the association between body mass index (BMI) at diagnosis and treatment outcome in children with acute lymphoblastic leukemia (ALL) have yielded inconsistent results. Hence, we conducted a retrospective study in a large cohort of Chinese children with ALL treated with contemporary protocols. Patients and Methods: A total of 1437 children (62.1% male; median age at diagnosis 5.7 years, range: 2.3–16.3 years) were enrolled in two consecutive clinical trials at the Shanghai Children's Medical Center. The rates of overall survival, event‐free survival, relapse, treatment‐related mortality, and adverse events were compared among patients who were underweight (BMI < 5th percentile), at a healthy weight (5th to 85th percentile), overweight (>85th to <95th percentile), and obese (≥95th percentile). Results: At diagnosis, 91 (6.3%) patients were underweight, 1070 (74.5%) were at a healthy weight, 91 (6.3%) were overweight, and 185 (12.9%) were obese. No significant association was found between weight status and 5‐year overall survival, event‐free survival, or relapse in the overall cohort. When analyzed as a continuous variable, a higher BMI Z‐score was associated with treatment‐related mortality (hazard ratio 1.33 (95% confidence interval [CI], 1.05–1.68%), p  = 0.02). The treatment‐related mortality rate was higher in the overweight (5.5%, 95% CI 0.8–10.2%) and obese (3.2%, 95% CI 0.6–5.8%) groups compared with the underweight (0.0%) and healthy‐weight groups (1.9%, 95% CI 1.1–2.7%; p  = 0.04). Multivariable analysis showed that children who were overweight had a higher risk of treatment‐related mortality (hazard ratio 3.8, 95% CI 1.3–11.4). Conclusion: While body weight status was not associated with event‐free survival or overall survival, overweight patients were at higher risk of treatment‐related mortality. Abstract : We found that overweight/obese children were at higher risk of treatment‐related mortality and developing severe toxicities than underweight or health‐weight children. Our findings reinforce the importance of the normalizing weight during the treatment period to improve survival and treatment outcomes.